2022
DOI: 10.29393/chjaa38-34stva10034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Growth of Socorro Island Merino Lambs

Abstract: The aims of this study were to evaluate the effect of genetic and non-genetic factors on the growth of Socorro Island Merino lambs and to model their growth curve using nonlinear mathematical models. The weight of 41 Socorro Island Merino lambs was recorded at birth and at 45, 90, 135, 180, 225, 270, 315 and 365 days of life from May 2019 to September 2021. The effects on growth of sex, genotype, year of birth, and parity of the dam were analyzed. Four non-linear models (Brody, Logistic, Gompertz and von Berta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Supporting our results, in the study of Boujenane [39], the best selected model (von Bertalanffy) revealed higher B values for twin or triplet Timahdite lambs. Some studies revealed higher K values for females than males [7,11,48,53] while some determined similar K values [39,54]. In our study, almost all the models predicted similar K values for both sexes.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Supporting our results, in the study of Boujenane [39], the best selected model (von Bertalanffy) revealed higher B values for twin or triplet Timahdite lambs. Some studies revealed higher K values for females than males [7,11,48,53] while some determined similar K values [39,54]. In our study, almost all the models predicted similar K values for both sexes.…”
Section: Discussionsupporting
confidence: 72%
“…These parameters can be evaluated before applying a robust selection to improve the slaughter characteristics of animals since body weight and the rate of weight gain are the most economically important parameters for sheep fattening [12]. In our study, all the models predicted higher A values for male lambs compared to female lambs, which could be explained by sexual dimorphism resulting in heavier adult weights for male lambs [7,11,48]. In the current study, all the models predicted higher A values for twin-born lambs.…”
Section: Discussionmentioning
confidence: 74%
“…As shown in Table 1 , Socorro Island Merino lambs do not clearly show sexual body size dimorphism during the first year of life, which is clearly expressed at later ages [ 15 ]. Recent investigations carried out with this same group of lambs showed this phenomenon in relation to their live weight, since this was only greater in males at 90 and 315 days [ 11 ]. This very research pointed out that the maturation rate of males, especially purebred ones, is slower compared to that of females, so that they take several years to reach puberty and adult weight.…”
Section: Discussionmentioning
confidence: 95%
“…The study was carried out at the Faculty of Veterinary Medicine and Animal Husbandry of the University of Colima, located in Tecomán, Colima, Mexico. The study included all 52 Socorro Island Merino lambs—13 purebred females, 14 purebred males, 9 crossbreed females, and 16 crossbreed males—born between 2019 and 2021, which were raised under a semi-intensive production system [ 11 ]. Crossbreed lambs belonged to F 3 and F 4 generations from crossbreeding Socorro Island Merino sheep with hair breeds such as Pelibuey, Katahdin, and Blackbelly ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation